Predictors of hepatitis C treatment response: what's new?. Issue 2 (February 2014) - Berry, Louise; Irving, Will
<x xml:space="preserve">Abstract</x> Hepatitis C virus infection is a growing, global health problem, with mortality expected to reach a peak in the next ten years in many western countries. A number of host and viral factors have been established as useful predictors of treatment response in the context of interferon and ribavirin. Several new markers have recently been identified that improve our understanding of treatment response. The addition of protease inhibitors to treatment regimens has highlighted the importance of viral kinetics on-treatment in predicting response to treatment. Many new classes of direct acting anti-virals are currently being developed and expected to be clinically available in the near future. Current predictors of treatment response will be redefined in the context of interferon free regimens.